Kinematic differences between uphill roller skiing and on-snow skiing using the V2 skating technique - Myklebust, H.; Losnegard, T.; Hallén, J. (European Journal of Applied Physiology, 2022)
Purpose Roller skiing is the primary sport-specific training and testing mode during pre-competition periods for cross-country skiers, biathletes, and Nordic combined athletes. The present study aimed to compare the kinematics between uphill roller skiing and on-snow skiing using the V2 sub-technique.